Basidiomycosis: a review of the literature - Lacaz, Carlos da Silva; Heins-Vaccari, Elisabeth Maria; Melo, Natalina Takashi de; Hernandez-Arriagada, Giovanna Letícia (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
The basidiomycosis, fungal infections provoked by basidiomycetes or agaric fungi have been recorded at growing frequencies in the medical literature, especially after the advent of AIDS in 1991. The basidiospores of these fungi, scattered in the atmosphere and transported by winds or air currents, reach the maxillary sinuses through the nasal route, most of the times causing signs and symptoms of chronic sinusitis. Basidiomycetes have also been isolated from sputum, especially Schizophyllum commune. Lesions of the buccal mucosa, brain abscesses, onychomycosis and endocarditis have been described, with a growing interest in this type of deep mycosis on the part of mycologists and infectologists. The present paper reports descriptions of mycetism as well as infectious processes caused by basidiomycetes, such as Schizophyllum commune, Ustilago maydis (= Ustilago zeae) and Coprinus cinereus